PENGARUH HIDROLOGI LAHAN PERTANIAN TERHADAP PRODUKTIVITAS PADI DI DAS OPAK-OYO - Setiawan, Bagus Arif; Suprayogi, Slamet; Purnama, Ig. L. Setyawan (Jurnal Swarnabhumi : Jurnal Geografi dan Pembelajaran Geografi, 2025)
The average productivity of ricefield at subdistricts in the Opak-Oyo watershed was fluctuated between 54.5 - 64.5 quintals/hectare in 2005-2017. This causes food insecurity considering that the food demand is always increasing between years. Crop productivity is generally effected by hydrological condition, application of technology, pests, and quality of seed. This research aims to study the effect of changes in land hidrology on rice productivity for each sub-district in the Opak-Oyo watershed. Hidrological analysis is carried out by calculating the water balance each year. The variables such as evapotranspiration, rainfall, water storage and it changes are compared with rice productivity in multiple linear regression analyisis. The results showed that the hydrological variables simultaneously impact on rice productivity with a regression value between 0.39 - 0.97 and above 0.7 in majority. Based on the coefficient value comparasion between variables in resulted equation, evapotranspiration tends to have a dominant impact in 57% of sub-districts, rainfall has a dominant impact in 9% of sub-districts, while water storage and it changes have a dominant impact in 34% of the subdistricts